Adoption of Chatbots for Learning among University Students: Role of Perceived Convenience and Enhanced Performance - Malik, Reena; Shrama, Ambuj; Trivedi, Sonal; Mishra, Rikkee (International journal of emerging technologies in learning, 2021)
With the advent of internet and exponentially growing smartphone market, chatbots are becoming popular and are being widely used for interactions in varied fields. This study investigated the usage of chatbots for educational/learning purpose by university students. Wide research has been done exploring usage of chatbots in service industry; still there is vacuum regarding usage of chatbots in education for effective learning. Using path analysis, the study demonstrates validation of two newly added constructs as an extension in Technology Adoption Model and tries to understand the antecedents for intension to adopt chatbots. This study is of utmost importance to researchers, policy makers, system designers for e- learning platforms, teachers, and students in order to make learning effective.